2011
DOI: 10.4103/0971-3026.90697
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of breast lesions using ultrasound elastography

Abstract: Context:The recent introduction of elastography has increased the specificity of USG and enabled early diagnosis of breast cancer. Quantitative elastography, especially with strain ratio (SR) index, improves diagnostic accuracy and decreased number of biopsies.Aims:The purpose of this study was to assess the role of USG elastography in the differential diagnosis of breast lesions.Settings and Design:This prospective study was conducted in the University of Medicine and Pharmacy Research Centre of Craiova.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 15 publications
3
10
1
2
Order By: Relevance
“…With this value, we found that the mean elasticity score was significantly higher in malignant masses than in benign masses. Our findings are concordant with other previous studies using 5-point scoring systems [ 10 , 23 , 25 ]. In VTQ mode, each breast lesion was differentiated as a benign or malignant lesion using SWV measurements; malignant lesions showed significantly higher SWV values than benign lesions.…”
Section: Discussionsupporting
confidence: 94%
“…With this value, we found that the mean elasticity score was significantly higher in malignant masses than in benign masses. Our findings are concordant with other previous studies using 5-point scoring systems [ 10 , 23 , 25 ]. In VTQ mode, each breast lesion was differentiated as a benign or malignant lesion using SWV measurements; malignant lesions showed significantly higher SWV values than benign lesions.…”
Section: Discussionsupporting
confidence: 94%
“…In some studies, a combination of elastography with CU improved differentiation between benign and malignant breast masse. [3,4] However, this result was not observed in the present study. ROC curve analyses showed that the diagnostic efficiencies of CU, SR + CU, and PHC + CU were not significant, yet the accuracy of each was significant according to the McNemar test.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies have reported that elastography has the potential to improve differentiation of benign and malignant masses. [3,4] There are 2 widely employed strain elastography evaluation methods: a scoring system and evaluation of strain ratio (SR). Regarding the former, there are different standards that have been used to score lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant masses are stiffer than the normal tissues, so measuring the tissue strain by compressing the sonography transducer provides information regarding the strain of breast lesions in relation to the surrounding fatty tissue (strain ratio) and breast lesion elasticity in SE compared to its length in B mode sonography (E/B ratio). 11,12 Moreover, color Doppler US helps to explore vascularity within the tumor and provides information regarding the angiogenesis in breast masses. 13 The current study is conducted to determine the diagnostic yield of conventional US, SE, and color Doppler US and different features of SE, including strain ratio and E/B ratio in differentiating malignant breast lesions.…”
Section: Introductionmentioning
confidence: 99%